The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1364/ol.41.004943
|View full text |Cite
|
Sign up to set email alerts
|

Classical spectral ghost ellipsometry

Abstract: We introduce a novel ghost reflection ellipsometer for a spectral characterization of homogeneous thin films and interfaces. The device makes use of a uniform, spatially incoherent, unpolarized light source with Gaussian statistics and of the detection of intensity correlations. Unlike traditional ellipsometers, no source or detector calibration and reference sample are needed. The method is also insensitive to instrumentation errors. The ellipsometer that we present here is a classical analog of a quantum twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Though the sensitivity of phase difference δ△ can not be obtained from intensity measurements for Fock states or NOON state, we are still able to study the same through the information encoded in the density matrix ρ(t). As shown in ( 21) and (32), only the off-diagonal terms contain the phase parameter △. The fidelity, i.e.…”
Section: Projective Measurements To Obtain Ord Ie Relative Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Though the sensitivity of phase difference δ△ can not be obtained from intensity measurements for Fock states or NOON state, we are still able to study the same through the information encoded in the density matrix ρ(t). As shown in ( 21) and (32), only the off-diagonal terms contain the phase parameter △. The fidelity, i.e.…”
Section: Projective Measurements To Obtain Ord Ie Relative Phasementioning
confidence: 99%
“…Several other studies have shown advantages of using squeezed light with tailored beams; SPDC photons in ellipsometry [39,40]. The ellipsometry with classically correlated beams was discussed in [32]. We briefly outline the organization of the paper here.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has particular potential for imaging under turbulent [4][5][6][7] or low-light-level conditions [8] as well as in harsh environments where conventional imaging methods are hard or impossible to implement [9]. Recently, ghost imaging has been demonstrated in such diverse applications as x-ray [10], atom [11], and neutron [12] imaging, as well as in encryption [13], spectroscopy [14], ellipsometry [15,16], and polarimetry using Stokes correlations [17].…”
Section: Introductionmentioning
confidence: 99%
“…The object is characterized through multiple coincidence or correlation measurements [17] that can deliver a better signal-to-noise ratio compared to classical imaging systems, and also enable imaging with a very low number of photons [18,19]. However, there remains a fundamental limitation of traditional ghost polarimetry approaches due to a need for multiple reconfigurable elements such as rotating waveplates [20][21][22][23][24][25][26][27]. Yet, the unique capabilities of polarization control with metasurfaces towards potential singleshot ghost imaging configurations remains largely untapped, so far limited to the incorporation of metasurfaces for hologram generation [28].…”
mentioning
confidence: 99%